Identification of transcripts with short stuORFs as targets for DENR•MCTS1-dependent translation in human cells - Schleich, Sibylle; Teleman, Aurelio A. (Scientific reports, 2017)
The non-canonical initiation factors DENR and MCTS1 have been linked to cancer and autism. We recently showed in Drosophila that DENR and MCTS1 regulate translation re-initiation on transcripts containing upstream Open Reading Frames (uORFs) with strong Kozak sequences (stuORFs). Due to the medical relevance of DENR and MCTS1, it is worthwhile identifying the transcripts in human cells that depend on DENR and MCTS1 for their translation. We show here that in humans, as in Drosophila, transcripts with short stuORFs require DENR and MCTS1 for their optimal expression. In contrast to Drosophila, however, the dependence on stuORF length in human cells is very strong, so that only transcripts with very short stuORFs coding for 1 amino acid are dependent on DENR and MCTS1. This identifies circa 100 genes as putative DENR and MCTS1 translational targets. These genes are enriched for neuronal genes and G protein-coupled receptors. The identification of DENR and MCTS1 target transcripts will serve as a basis for future studies aimed at understanding the mechanistic involvement of DENR and MCTS1 in cancer and autism.